Triglyceride-glucose index is associated with microcirculatory resistance in patients with type 2 diabetes and STEMI undergoing primary PCI - Guoyu Wang; Cen Xu; Jian Wang; Zhimei Teng; Xiang Sha; Kai Xu; Ruzhu Wang; Li Zhu (Scientific Reports)
Abstract The triglyceride-glucose (TyG) index is emerging as a promising marker for insulin resistance and serves as an independent risk predictor for cardiovascular outcomes. The coronary angiography-derived index of microcirculatory resistance (AMR) is computed to evaluate coronary microcirculation. However, the association between the TyG index and the AMR in patients with type 2 diabetes mellitus (T2DM) and ST-segment elevation myocardial infarction (STEMI) remains unclear. We consecutively recruited 168 patients with T2DM and STEMI who underwent primary percutaneous coronary intervention (pPCI) at Taizhou People’s Hospital from January 2022 to December 2023. Patients were classified into low AMR group (AMR < 2.5) and high AMR group (AMR ≥ 2.5). The TyG index was calculated using the formula: ln [plasma triglyceride (mg/dL) × fasting blood glucose (mg/dL)/2]. The study enrolled 81 patients in the low AMR group and 87 in the high AMR group, with the TyG index being significantly higher in the high AMR group. Multivariable logistic regression analysis revealed a significant association between the TyG index and high AMR after adjusting for confounding variables (odds ratio: 2.449, 95% confidence interval: 1.421–4.220, and p = 0.001). The area under the curve for the TyG index predicting high AMR was 0.650 (95% confidence interval: 0.57–0.73, p < 0.001), with a cut-off value of 9.57. Our findings indicate that the TyG index is significantly associated with AMR in T2DM patients with STEMI undergoing pPCI, suggesting it may serve as a valuable predictor of high AMR in this population.